2016
DOI: 10.1016/j.advwatres.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic advection at the pore scale: Mechanisms, upscaling and implications for macroscopic transport

Abstract: The macroscopic spreading and mixing of solute plumes in saturated porous media is ultimately controlled by processes operating at the pore scale. Whilst the conventional picture of pore-scale mechanical dispersion and molecular diffusion leading to persistent hydrodynamic dispersion is well accepted, this paradigm is inherently two-dimensional (2D) in nature and neglects important three-dimensional (3D) phenomena. We discuss how the kinematics of steady 3D flow at the porescale generate chaotic advection-invo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Recent studies [24][25][26] have also established that chaotic mixing is inherent to three-dimensional (3D) porous media for which the solid phase is continuous (i.e., not granular), such as open porous networks. While such chaotic mixing is driven by the topological complexity inherent to all porous media, it is unknown whether these concepts apply to discrete porous media as their topology is now contingent upon pointlike contacts between grains.…”
mentioning
confidence: 99%
“…Recent studies [24][25][26] have also established that chaotic mixing is inherent to three-dimensional (3D) porous media for which the solid phase is continuous (i.e., not granular), such as open porous networks. While such chaotic mixing is driven by the topological complexity inherent to all porous media, it is unknown whether these concepts apply to discrete porous media as their topology is now contingent upon pointlike contacts between grains.…”
mentioning
confidence: 99%
“…Thus this explicit representation in terms of the velocity magnitude is not possible for non-integrable steady 3-D flows such as pore-scale 3-D Stokes flow or 3-D tensorial Darcy flow as the helicity density h is non-zero for these flows, and so there do not exist a pair of linearly independent invariants (ψ 1 , ψ 2 ). Indeed, this property is a necessary condition for pore-scale 3-D flow to exhibit chaotic advection (Lester, Trefry & Metcalfe 2016b).…”
Section: Integrability Of Scalar Darcy Flowmentioning
confidence: 99%
“…Recent studies (Lester et al 2016b;Turuban et al 2018Turuban et al , 2019Souzy et al 2020) have established that chaotic advection is inherent to steady 3-D Stokes flow at the pore-scale, even in a medium that is homogeneous at the pore scale, providing a decisive link between pore-scale structural properties and the Lagrangian kinematics of porous media (Heyman et al 2020;Heyman, Lester & Le Borgne 2021). This result is not surprising as the Poincaré-Bendixson theorem states that only continuous systems with three or more degrees-of-freedom (DOFs) can admit a chaotic dynamics, hence, chaos is possible in three dimensions but not 2-D steady pore-scale flow.…”
Section: Integrability Of Scalar Darcy Flowmentioning
confidence: 99%
“…compressible Darcian systems where engineered pumping activity is absent. Dynamical systems concepts have also been used to link the topology of pore-scale architectures with pore-scale solute mixing and macroscopic transport phenomena (Lester et al, 2013b(Lester et al, , 2014b(Lester et al, , 2016b, resulting in fundamental upscaling behaviours conditioned on the details of pore-scale Lagrangian structures. These mechanisms have recently been confirmed via direct experimental observations of pore-scale mixing (Souzy et al, 2020;Heyman et al, 2021Heyman et al, , 2020, leading to the highly striated solute distributions shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%